Agriculturists Personal and Business Use of Online Communication Tools - Kelsey Shaw; Courtney Meyers; Erica Irlbeck; David Doerfert; Katie Abrams; Chris Morgan (Journal of Applied Communications, 2015)
New programs and efforts are being promoted to help American farmers and ranchers succeed in their efforts, both in their daily operations and in their attempts to reach consumers. Online communication tools may be one way agriculturists can share their stories and market directly to these audience members, but much is unknown regarding the extent to which these tools are being implemented. The purpose of this study was to determine agriculturists’ current use of online communication tools for both personal and business purposes. The target population for this study was members of organizations that serve young and/or beginning farmers and ranchers in three states. An online survey was administered electronically to members of seven organizations, and 185 completed questionnaires were analyzed. The findings indicated websites and Facebook are the commonly used online communication tools for personal and business use. Many tools are not used at all for either purpose. A significant correlation was found between the use of online communication tools in personal and business settings. Additional research is needed to further explore agriculturalists’ use of these tools for both purposes.
Keywords: Social media; online communication; farmers; ranchers